First report of imidazolinone-resistant Bassia scoparia in Argentina : evidence from dose-response bioassays and ALS gene sequencing - Montoya, Jorgelina Ceferina; Fabressi, Esteban E.; Yanniccari, Marcos (Universidad de Concepción, Chile, 2025)
Kochia (Bassia scoparia (L.) A. J. Scott.) is a problematic weed. In Argentina, farmers have recently experienced poor control over imidazolinone-resistant sunflowers, specifically the sensitivity of putative kochia resistant plants to imidazolinone herbicides. Seeds from putative resistant populations from Pellegrini (P), De Bary (DB), and 30 de Agosto (A) and a known susceptible (S) population from Col. Martín Fierro were sown in pots. A mixture of imazapyr (Clearsol® WG 80%) and imazamox (Trigosol WG 70%) was sprayed when plants reached approximately 6 cm in height and 10-leaf stage using a boom sprayer. A trial was conducted to determine the response of kochia to the recommended doses (1x) of imazapyr 80.00 g ai ha-1 + imazamox 20.30 g ai ha-1. Plants were harvested 30 days after treatment to determine fresh shoot weight. A dose–response experiment was performed using imazapyr + imazamox at concentrations of 0x, 1/4x, 1/2x, 1x, 2x, 4x, and 8x. Partial ALS gene amplification was performed using leaves of plants that survived an 8x dose. The 1x fresh weight of the putative populations did not differ from 0x. LD50 of imazapyr+imazamox (g ai ha-1) for each biotype was: S, 18.86 + 4.79; DB, 82.48 + 20.93; A, 179.36 + 45.51; and P, 550.88 + 139.79. The three resistant populations exhibited a single-point mutation from guanine to thymine, detected in codon 574 of the ALS gene. This mutation confers resistance to ALS inhibitors. This is the first reported case of kochia resistance in Argentina, providing valuable insights that extend beyond sunflower weed management.